2018
DOI: 10.1007/jhep01(2018)148
|View full text |Cite
|
Sign up to set email alerts
|

Integrable systems with BMS3 Poisson structure and the dynamics of locally flat spacetimes

Abstract: We construct a hierarchy of integrable systems whose Poisson structure corresponds to the BMS 3 algebra, and then discuss its description in terms of the Riemannian geometry of locally flat spacetimes in three dimensions.The analysis is performed in terms of two-dimensional gauge fields for isl(2, R), being isomorphic to the Poincaré algebra in 3D. Although the algebra is not semisimple, the formulation can still be carried out à la Drinfeld-Sokolov because it admits a nondegenerate invariant bilinear metric. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 111 publications
(158 reference statements)
0
44
0
Order By: Relevance
“…[10][11][12][13][25][26][27][28][29][30][31][32]. In the context of three-dimensional gravity, it has been shown that the anisotropic scale invariance can also be induced by suitable choices of boundary conditions [33][34][35][36][37][38]. In two spacetime dimensions, field theories with anisotropic scaling have also been discussed in e.g.…”
Section: Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][25][26][27][28][29][30][31][32]. In the context of three-dimensional gravity, it has been shown that the anisotropic scale invariance can also be induced by suitable choices of boundary conditions [33][34][35][36][37][38]. In two spacetime dimensions, field theories with anisotropic scaling have also been discussed in e.g.…”
Section: Contentsmentioning
confidence: 99%
“…As expected, in the isotropic case (z = 1) the conformal transformation (3.29) becomes local. In fact, in this case the function in (3.30) reads 34) and hence (3.29) and (3.31) reduce to the transformation law and the generators of the conformal symmetry of the Floreanini-Jackiw action [9], given by…”
Section: Conformal Algebra From a Nonlocal Symmetrymentioning
confidence: 99%
“…Other examples of this relationship between 2D integrable systems and gravity in 2+1, have been also made for the cases of "flat" and "soft hairy" boundary conditions in[25] and[26], respectively.…”
mentioning
confidence: 99%
“…As an ending remark, it is worth mentioning that different classes of boundary conditions relating three-dimensional gravity with integrable systems have been proposed in [30][31][32][33]. It would be interesting to explore whether a similar construction, as the one performed here, could be carried out in those cases.…”
Section: Discussionmentioning
confidence: 90%